Validating a second-order model for oil and gas projects’ investment climate scale - Mas’ud, Abdulsalam; Abdul Manaf, Nor Aziah; Saad, Natrah (Emerald Publishing Limited, 2017)
Purpose The investment climate is one of the key factors considered by foreign investors while deciding their investment destination.This paper aims to attempt at validating the second-order model of oil and gas projects’ investment climate. Examination of the relationship between the dimensions of oil and gas projects’ investment climate; strategy, participants/operating environment and risk/return; and the overall latent construct was conducted. The study also evaluates the goodness of fit of the second-order model using relevant fit indices Design/methodology/approach Oil and gas experts in Malaysian marginal oil fields sub sector were deployed, through whom responses were collected that formed the data set used in the analysis. Then, the data were used for confirmatory factor analysis, evaluation of the second-order model through path analysis and for model fit evaluation.Findings The finding revealed that the second-order model of oil and gas projects’ investment climate is valid and reliable.It also revealed that all the three dimensions, strategy, participants/operating environment and risk/return, have significant effects on the formation of the oil and gas projects’ investment climate.Finally, the goodness of fit of the second-order model satisfied the relevant fit indices.Research limitations/implications The findings present valuable insights to policymakers on the extent of the influence each of the dimensions has on the overall latent construct.The validity and reliability analysis suggests the measurements of the second-order model of oil and gas projects’ investment climate construct, and its dimensions are valid, reliable and fit for future empirical research. Thus, it calls for replication in other oil and gas settings.Originality/value The findings from the results of this study are pioneering. Extant literature falls short in attempting the validation of the second-order oil and gas projects’ investment climate scale, as well as relating each of the dimensions with the overall latent construct.